KUALITAS PELAYANAN DI RSUD UNDATA SULAWESI TENGAH (STUDI PASIEN RAWAT INAP KELAS III) - Ariny, Nur (Katalogis, 2017)
The purpose of this study was to analyze the quality of public service viewed from tangible, realibility, responsiveness, assurance, and empathy aspects at Undata Regional Public Hospital of Central Sulawesi, the case study of third-class inpatient. The types of data used were primary and secondary data. Data were collected through observation, interview, and documentations techniques. The informans of the study were determined using purposive sampling method, resulting in 7 people comprising 2 head of mursing division, 1 nurse, and 4 patients. The techniques of data analysis used were data reduction, data presentation,and conclusion. The theory used was the theory of Parasuraman in Tangkilisan. The result showed that there were some service which had been good and some ones which were dissatisfactory, but the average had been good. It was known from the five aspects: the physical evidence (tangible), facilities and infrasructure were inadequate, such as toilets’ condition, but officers’ performance had been good; the realibility, officers’ ability to provide service had shown good result, diagnoses made by specialist doctors had been right in accordance with symptoms and complaints felt by patients; the responsiveness, officers’ accountability to patients had shown good results, it could be viewed from officers’ willingness to help and provide service quickly and officers’ alacrity in dealing with patient complaints; the assurance, knowledge and background of officers had been in accordance with education levels pursued by officers, and officers’ politeness to patients had shown good results; and the empathy, attentions given by officers had been good and equal to one another, not dicriminating between statuses and groups.